A Low Total Psoas Muscle Area Index Is a Strong Prognostic Factor in Metastatic Pancreatic Cancer. Issue 4 (April 2021) - Williet, Nicolas; Fovet, Marion; Maoui, Khawla; Chevalier, Clément; Maoui, Meriem; Le Roy, Bertrand; Roblin, Xavier; Hag, Bachir; Phelip, Jean-Marc
Abstract : Objectives: The total psoas area index (TPI) is an emerging alternative to the total skeletal muscle area index as a prognostic factor but has never been evaluated in metastatic pancreatic cancer (mPC). Methods: Areas were manually recorded, as previously described. Sex-specific cutoffs were identified by optimum stratification of TPI using log-rank χ 2 statistic associated with mortality to define sarcopenic psoas. Progression-free survival (PFS) and overall survival (OS) were the primary objectives. Two period groups were used as internal validation. Results: During the period study, 79 patients were treated for mPC. The TPI was correlated with PFS (hazards ratio, 0.81; P = 0.02) and OS (hazards ratio, 0.7; P < 0.001). Optimum thresholds defining sarcopenic psoas were less than 5.73 cm 2 /m 2 in men and less than 4.37 cm 2 /m 2 in women. Patients with sarcopenic psoas (62.0%) had shorter median PFS (2.9 months) compared with the others (6.6 months, adjusted P log-rank = 0.01), independently to the intensity of chemotherapy, weight loss, and performance status greater than 1. Similarly, OS was independently shorter in patients with sarcopenic psoas (7.6 months) versus the others (22.2 months, adjusted P < 0.001). These results were confirmed in the 2 period groups. Conclusions: A low TPI is a stronger independent prognostic factor in mPC. Abstract : Supplemental digital content is available in the text.